2019
DOI: 10.1165/rcmb.2018-0053oc
|View full text |Cite
|
Sign up to set email alerts
|

IL-13–regulated Macrophage Polarization during Granuloma Formation in anIn VitroHuman Sarcoidosis Model

Abstract: The mechanisms underlying abnormal granuloma formation in patients with sarcoidosis are complex and remain poorly understood. A novel in vitro human granuloma model was used to determine the molecular mechanisms of granuloma-genesis in patients with sarcoidosis in response to putative disease-causing mycobacterial antigens. Peripheral blood mononuclear cells (PBMCs) from patients with active sarcoidosis and from normal, disease-free controls were incubated for 7 days with purified protein derivative (PPD)-coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 37 publications
(38 reference statements)
7
50
1
2
Order By: Relevance
“…Macrophage features observed in our in vitro human granuloma model strongly align with this theory, including a significant increase in >50 different M2-like macrophage gene transcripts and elevated expression of CD163 in sarcoidosis granulomas at the protein level ( Figure 5 ). Pathway analysis predicted the cytokine IL-13 as being an important upstream regulator of the observed gene expression changes in sarcoidosis compared to healthy controls after antigen stimulation, and we verified this gene network to be highly overrepresented in human sarcoidosis lung and lymph node tissues ( 45 ) ( Figure 6 ). IL-13 signaling is associated with a Th2-biased immune response and is a known promoter of alternative or M2-like macrophage activation ( 46 , 47 ).…”
Section: Modeling Macrophage Responses In Sarcoidosismentioning
confidence: 57%
See 1 more Smart Citation
“…Macrophage features observed in our in vitro human granuloma model strongly align with this theory, including a significant increase in >50 different M2-like macrophage gene transcripts and elevated expression of CD163 in sarcoidosis granulomas at the protein level ( Figure 5 ). Pathway analysis predicted the cytokine IL-13 as being an important upstream regulator of the observed gene expression changes in sarcoidosis compared to healthy controls after antigen stimulation, and we verified this gene network to be highly overrepresented in human sarcoidosis lung and lymph node tissues ( 45 ) ( Figure 6 ). IL-13 signaling is associated with a Th2-biased immune response and is a known promoter of alternative or M2-like macrophage activation ( 46 , 47 ).…”
Section: Modeling Macrophage Responses In Sarcoidosismentioning
confidence: 57%
“…Other data from the model that point to a functional imbalance in favor of Th2-immune signaling in sarcoidosis was the relatively blunted INF-γ production associated with sarcoidosis following M.tb antigen stimulation and the significant inhibition of granuloma formation in sarcoidosis through pharmacologic signal transducer and activator of transcription 6 (STAT6) inhibition (45). IL-13-mediated activation of STAT6 is a well-established pathway for M2-like macrophage polarization (52).…”
Section: Modeling Macrophage Responses In Sarcoidosismentioning
confidence: 99%
“…However, while tAMs from naive mice express the receptor for GM-CSF [ 19 ], IL-13, and IL-33, we did not observe the expression of TSLPR or IL-17RB (the specific receptor chain involved in the formation of the IL-25 receptor) in steady state alveolar macrophages, therefore limiting our study to IL-13 and IL-33. Intriguingly, IL-13 has been reported to act as an inducer of fusion-driven MNGC formation [ 5 ] and contributes to macrophage polarization in sarcoidosis-associated granuloma formation in vitro [ 39 ]. However, in tAMs, our data suggest that IL-13 drives polyploidy.…”
Section: Discussionmentioning
confidence: 99%
“…Crouser et al showed that macrophages from sarcoidosis patients maintained a M2 phenotype in the presence of PPD beads compared to non-coated beads, compared to control patients for whom macrophages acquired M1 characteristics [ 60 ]. Likewise, Locke et al showed an increase in M2 polarization with the expression of CD163 and an IL13 gene expression profile in sarcoidosis patients compared to control patients in response to PPD beads [ 61 ]. In the MAB model, granuloma formation was observed 72 h after exposure with a marked Th1 and Th17 signature and NFκB activation [ 62 ].…”
Section: In Vitro Modelsmentioning
confidence: 99%